Thermal uniformity analysis of a hybrid battery pack using integrated phase change material, metal foam, and counterflow minichannels - Najafi Khaboshan, Hasan; Kadirgama, Kumaran; Ramasamy, Devarajan; Talele, Virendra; Zhao, Peng; Tyagi, Harsh; Miljkovic, Nenad (Elsevier Ltd, 2025)
This study investigates the thermal performance and temperature uniformity of a hybrid battery thermal management system (BTMS) that integrates phase change material (PCM), metal foam, and minichannels. Computational fluid dynamics is used to model the PCM melting process and heat transfer between all components. The primary goal of the work is to investigate BTMS architectures which can enhance thermal uniformity and prevent critical temperature rise in a high-voltage battery pack under fast discharging and real-world driving cycle. Four BTMS designs are compared. The design that integrates PCM, metal foam, and counterflow minichannels is shown to have the best performance. At low pumping power (coolant Reynolds number Re = 10), this design reduces the peak battery temperature by 11.5 K compared to a design employing pure PCM only. This configuration also ensures a temperature difference of less than 5 K among individual battery cells, addressing thermal safety considerations and extending battery lifespan. Further analysis revealed that the inclusion of metal foam delays PCM melting, enhances both system and battery thermal uniformity, and offers a higher performance-to-weight ratio compared to designs without metal foam. Although wavy-shaped minichannels offer minimal temperature improvement (0.3 K) over straight minichannels, their higher cost and increased pumping power requirements do not justify their practicality. Under both fast discharging and real driving conditions, the first design with pure PCM provides uniform heat distribution within batteries but fails to maintain the maximum battery temperature within the optimal range. Overall, this study highlights the effectiveness of the proposed hybrid BTMS design in providing uniform temperature distribution and maintaining the maximum battery temperature within the optimal range under harsh environmental conditions, fast discharging, and the Urban Dynamometer Driving Schedule (UDDS) drive cycle.